Numerical solution of Stokes problem for free convection effects in dissipative dusty medium. (30th December 2004) - Venkataraman, V.; Kannan, K.
Abstract : The flow past an infinite vertical isothermal plate started impulsively in its own plane in a viscous incompressible two-phase fluid has been considered by taking into account the viscous dissipative heat. The coupled nonlinear equations governing the flow are solved for fluid and particle phases by finite difference method. The velocity and temperature fields have been shown graphically forG being positive for dusty air and it was observed that the same results hold for water. (G denotes the Grashof number andG > 0 corresponds to cooling of the plate by free convection currents.) The results forG < 0 (heating of the plate) have been verified and discussed. The numerical values of skin friction and the rate of heat transfer of dusty fluid are shown in tables. The effects ofG andE (the Eckert number) on the flow field are discussed. It is observed that dusty fluid causes an increase in skin friction. The increase in mass concentration of dust particles decreases the heat transfer rate. The presence of inert particles does not admit the reverse type of flow even for large values oft .